If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23s + 14 = 65 Reorder the terms: 14 + 23s = 65 Solving 14 + 23s = 65 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 23s = 65 + -14 Combine like terms: 14 + -14 = 0 0 + 23s = 65 + -14 23s = 65 + -14 Combine like terms: 65 + -14 = 51 23s = 51 Divide each side by '23'. s = 2.217391304 Simplifying s = 2.217391304
| 3y^2-2x^2+2xy-6=0 | | 14x+3x+7x= | | 3.2=1.35h | | 2(j-20)+3=10 | | 3*1+y=9 | | 3*4+y=9 | | y-9=-11-y | | 4p-24=27-13p | | m-56=101 | | 3y+7=2y+7 | | 2y-5x=-60 | | w^2-9w+2=0 | | 4xsquared+3x+2x= | | o=364-120 | | (8x-4)-(9n-1)=12 | | C^2=0 | | 6(X+2)=2x+10 | | 15=-3(h-1)+9 | | 364=120+o | | 45y+11=20-54 | | 3(y+2)=15-y | | 2x-3=24x-135 | | 4(5p+6)=124 | | 6-y=20-4y | | 2y+3=11+y | | 2x+4x-3=11x-1 | | 4m+4m+2m+1+2m+3= | | 2.8=x-3.7 | | 2y+3=11+x | | -5t^3+22t^2-26t+14=0 | | 4B^3-12B^2-40B=0 | | 6t^2-11t-7=0 |